2014
DOI: 10.1088/0067-0049/214/1/12
|View full text |Cite
|
Sign up to set email alerts
|

Gpupegas: A New Gpu-Accelerated Hydrodynamic Code for Numerical Simulations of Interacting Galaxies

Abstract: In this paper a new scalable hydrodynamic code GPUPEGAS (GPUaccelerated PErformance Gas Astrophysic Simulation) for simulation of interacting galaxies is proposed. The code is based on combination of Godunov method as well as on the original implementation of FlIC method, specially adapted for GPU-implementation. Fast Fourier Transform is used for Poisson equation solution in GPUPEGAS. Software implementation of the above methods was tested on classical gas dynamics problems, new Aksenov's test and classical g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…9 showing the simlation of the collision of two galaxies according to the described two-phase model. The details of the problem statement and simulation results can be found in [35]. …”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…9 showing the simlation of the collision of two galaxies according to the described two-phase model. The details of the problem statement and simulation results can be found in [35]. …”
Section: Simulation Resultsmentioning
confidence: 99%
“…This approach has some limitations if it is necessary to trace a single particle and not a group of particles (for example, in the study of planet formation). But for the simulation of interacting galaxies this approach was successfully tested [35]. As it was already said in the introduction, the statement of the problem for the galactic objects dynamics is the solution of the equation of the gravitational magnetic gas dynamics for the gas component considering magnetic field and self-gravity and also the solution of the equations for the first moments of the collisionless Boltzmann equations.…”
Section: Co-design Of Parallel Numerical Methods For Astrophysicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison of different codes for subsonic turbulence is presented in [13]. Classical methods for simulation of magnetohydrodynamic turbulence such as adaptive mesh refinement (AMR) and smoothed-particle hydrodynamics are still widely used, but in recent years an impressive range of new methods have been proposed (a good review of these methods can be found in [14][15][16]). …”
Section: Introductionmentioning
confidence: 99%